MOVIE ANALYSIS WITH TERRORISM DEED USING ANALYSIS OF MOVIE TO SUPPORT STATE DEFENSE (FILM 22 MINUTES) - Deddy Stevano H. Tobing (Politeknik Negeri Media Kreatif, 2020)
This research is a follow-up study using film analysis theory to support national defense developed by Tobing, Deddy (2015) which emphasizes that films that are part of the mass media can be used to strengthen national defense. One of the threats in national defense is terrorism. The 22 Minutes film is a docudrama-type film which reviews the terrorist acts that took place in the Tamrin area of Central Jakarta on January 14, 2016. The film illustrates how terrorist acts take their toll on the police and the general public. In the end, this film shows actions to combat terrorism by using all the attributes of the Indonesian National Police forces.